Karakterisasi Morfologi Anggrek (Orchidaceae) di Hutan Kecamatan Ngaliyan Semarang - Hasby Ash Shidiqy; Baiq Farhatul Wahidah; Nur Hayati (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2018)
Orchid is one ofthe flowering plants with a very high level of diversity, including the diversity of morphological characters it has. This study aims to determine the diversity of orchids (orchidaceae) seen morphologically in the Ngalian sub-district forest in Semarang city. The method used in this study is cruise method and characterization techniques. Analysis of research data was carried out descriptively and displayed in the form of tables and photos. Orchids in the teak forest cover 940 ha, spread in 4 villages, namely Wonosari village, Gondoriyo village, Podorejo village and Wates village. The results showed that there were 3 types of orchid plants (orchidaceae). The types of orchids include Rhynchostylis retusa (L.) Bi., Rhynchostylis gigantea (Lindl.) Rindl. and Dendrobium crumenatum (L.) Sw. The diversity of morphological characters in each species of orchid such as diversity in leaf color, leafshape, leaftip shape, stem color, root type etc.